2010
DOI: 10.1016/s1734-1140(10)70365-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurosteroids on the human corticotropin-releasing hormone gene

Abstract: Increased activity of hypothalamic-pituitary-adrenal (HPA) axis and hypersecretion of corticotropin-releasing hormone (CRH) are known to be important factors in pathogenesis of some stress-related diseases. Some neurosteroids exert anxiolytic and antidepressant effects probably by inhibition of HPA axis activity. The aim of our study was to find out if neurosteroids can directly affect human CRH gene transcription. The effect of allopregnanolone (ALLO), allotetrahydrodeoxycorticosterone (THDOC), pregnenolone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Furthermore, a decrease in CRH mRNA expression following administration of AL alone may suggest a preventive silencing effect on HPA axis activity at the molecular level. Budziszewska et al (2010) found that AL inhibited CRH gene promoter activity in the differentiated Neuro-2A cells and suggested that the inhibition of CRH gene transcription may be a molecular mechanism responsible, at least partly, for its stress-protective effects. Similarly, such a situation may be related to the reduced expression of CRH and AVP receptors mRNA, as well as POMC mRNA in the AP, since some data point also to the involvement of other possible AL targets, such as intracellular nuclear receptors, protein kinases and microtubule-associated protein (Plassart-Schiess & Baulieu 2001).…”
Section: :1mentioning
confidence: 97%
“…Furthermore, a decrease in CRH mRNA expression following administration of AL alone may suggest a preventive silencing effect on HPA axis activity at the molecular level. Budziszewska et al (2010) found that AL inhibited CRH gene promoter activity in the differentiated Neuro-2A cells and suggested that the inhibition of CRH gene transcription may be a molecular mechanism responsible, at least partly, for its stress-protective effects. Similarly, such a situation may be related to the reduced expression of CRH and AVP receptors mRNA, as well as POMC mRNA in the AP, since some data point also to the involvement of other possible AL targets, such as intracellular nuclear receptors, protein kinases and microtubule-associated protein (Plassart-Schiess & Baulieu 2001).…”
Section: :1mentioning
confidence: 97%
“…In brain and peripheral tissue DOC is converted to THDOC by enzymatic A-ring reduction by the 5α-Reductase and 3α-Hydroxysteroid oxidoreductase activity. THDOC lacks classical steroid hormone properties, but activates the post-synaptic inhibitory GABA A -(γ-aminobutyric acid) receptor function on CRH expression (Reddy 2006) and suppress stress-induced HPA axis activity in rats (Budziszewska et al, 2010). Acute stress triggers a rapid and robust increase in circulating and brain levels of THDOC (Purdy et al, 1991).…”
Section: Regulation Of Corticosteroid Plasma Levelsmentioning
confidence: 99%
“…For example, allopregnanolone decreased anxiety in response to heat stress and administration of CRH (Patchev et al, 1994, 1996). A recent report indicated that physiological concentrations of allopregnanolone, THDOC, and pregnenolone in cell culture inhibited CRH reporter gene activity and forskolin-stimulated transcription (Budziszewska et al, 2010). Overall, these data are consistent with the idea that endogenous GABAergic neuroactive steroids exert negative feedback on stress responses.…”
Section: Neuroactive Steroid Regulation Of the Hpa Axis And Interactimentioning
confidence: 99%